NAD+ in Alzheimer’s Disease: Molecular Mechanisms and Systematic Therapeutic Evidence Obtained in vivo - Wang, Xinshi; He, Hai-Jun; Xiong, Xi; Zhou, Shuoting; Wang, Wen-Wen; Feng, Liang; Han, Ruiyu; Xie, Cheng-Long (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria in neurons generate adenosine triphosphate (ATP) to provide the energy required for constant activity. Nicotinamide adenine dinucleotide (NAD+) is a vital metabolite involved in cellular bioenergetics, mitochondrial homeostasis, ATP production and adaptive stress responses. Exploration of the biological functions of NAD+ has been gaining momentum, providing many crucial insights into the pathophysiology of age-associated functional decline and diseases, such as Alzheimer’s disease (AD). Here, we systematically review the key roles of NAD+ precursors and related metabolites in AD models and show how NAD+ affects the pathological hallmarks of AD and the potential mechanisms of action. Advances in understanding the molecular roles of NAD+-based neuronal resilience will result in novel approaches for the treatment of AD and set the stage for determining whether the results of exciting preclinical trials can be translated into the clinic to improve AD patients’ phenotypes.